국제결혼중개에 있어서 제공대상인 신상정보의 내용과 그 개선방향 연구 - 송시우 (입법학연구, 17(1), 2020)
오늘날 우리사회에는 해마다 약 2만여 쌍의 다문화가족이 탄생하고 있다. 그 중 상당수는 국제결혼중개업자의 중개행위로 이루어지는 것이 현실이다. 그런데 여성가족부에 의하여 실시된 2014년과 2017년의 국제결혼실태조사의 결과에 따르면, 국제결혼중개업자로부터 배우자를 소개받았을 때 받은 신상정보와 결혼 후 알게 된 정보가 달랐다고 상당수가 답하였을 뿐만 아니라 이로 인하여 결혼 후에도 배우자와의 갈등을 겪었다고 답한 자들이 상당수라는 점에서 신상정보의 정확성이 매우 중요하다는 점을 알 수 있다. 현행 결혼중개업법에서는 국제결혼중개업자에게 신상정보제공의무를 부여하고 있다. 그리고 제공되어야 하는 신상정보로는 혼인경력, 건강상태, 직업, 범죄경력 및 그 밖에 상대국의 법령에서 정하고 있는 사항인데, 그 규정 내용의 불완전성이 주장되어지고 있다. 이에 본 논문은 결혼중개업법 제10조의2에서 규정한 신상정보들의 내용을 점검하고 대안을 제시하기 위한 것이다. 1. 먼저 제공되어야 할 신상정보의 각각의 내용을 점검하여 보면, ① ‘혼인경력’과 관련하여서는 현행 법률과 시행령의 해석상으로는 혼인관계증명서 또는 가족관계증명서 어느 한가지로 증명하도록 하고 있다. 그러나 미혼모‧미혼부의 경우처럼 혼인은 한 적은 없으나 자녀가 있는 경우, 이로 인한 가정파탄의 결과가 나타날 수 있다는 점에서, 혼인관계상세증명서 ‘및’ 가족관계상세증명서 양자를 모두 신상정보제공대상으로 삼는 것이 타당하다고 판단하였다. ② ‘건강상태’의 경우는 최근 증가되고 있는 추세인 마약류중독과 관련된 내용의 보강이 필요하다. ③ ‘직업’은 국제결혼중개업체에게 그 진위여부의 확인의무를 부과할 필요가 있다. 다만 진위확인 결과 허위로 확인된 경우에는 국제결혼중개업자는 결혼중개를 거부하도록 현행법이 정하고 있다는 점에서 개정의 필요성까지는 보이지 아니한다. ④ ‘범죄경력’ 역시 마약류중독과 관련된 범죄를 추가할 필요성이 크다. 2. 다음으로 신상정보의 제공시기는 명문으로 규정되어 있지는 아니하나, 첫 만남 이전에 제공되어야 한다는 것이 우리 법원의 태도이며 입법 역시도 그렇게 해석되어진다. 이는 예외없이 첫 만남 이전이어야 한다고 판단된다. 3. 신성정보의 공증은 양 당사자가 제시한 신상정보의 정확성을 담보하기 위한 것으로서, 외국에서 즉 대한민국 외의 국가에서 공증인의 인증을 받은 경우에는 재외공관의 공증담당영사로부터 확인을 받도록 함이 타당하다. 이러한 방식으로 국제결혼과정에서의 신상정보의 내용을 강화함은 국제결혼중개를 통하여 형성된 다문화가족의 안정적인 결혼생활을 누릴 수 있도록 중요한 역할을 할 것이라 판단된다. Today, about 20,000 pairs of multicultural families are born each year in our society. Many of them are made up of intermediary acts by international marriage brokers. However, according to the results of the International Marriage Survey in 2014 and 2017, not only did the personal information received when receiving a spouse's introduction from an international marriage broker differ from that obtained after marriage, but also caused conflicts with the spouse after marriage. The accuracy of personal information is very important in that many respondents said they have suffered. The current 「Marriage Brokers Business Management Act」 gives international marriage brokers an obligation to provide personal information. Personal information to be provided is prescribed by marriage history, health condition, occupation, criminal history and other laws and regulations of the other country. The purpose of this paper is to examine the contents of personal information provided in Article 10-2 of the 「Marriage Brokers Business Management Act」 and to suggest alternatives. 1. Check each piece of personal information that should be provided first, ① In relation to 'marriage history', the current law requires either marriage certificate or family relationship certificate. However, as in the case of unmarried mothers and single mothers, there is no single marriage, but if there are children, the consequences of family breakdown may occur. It was reasonable to use both marriage certificate and family relationship certificate as the subject of personal information. ② In case of 'health condition', it is necessary to reinforce the contents related to drug addiction, which is increasing recently. ③ 'Occupation' needs to impose an obligation on the international marriage broker to confirm its authenticity. ④ ‘Criminal history’ also needs to add crime related to drug addiction. 2. Next, the timing of providing personal information is not prescribed in writing, but it must be provided before the first meeting. This is the court's attitude, and legislation is interpreted as it is. It is believed that this should be before the first meeting without exception. 3. The notarization of divinity information is to ensure the accuracy of the personal information presented by both parties. If a notary public is certified in a foreign country, that is, outside the Republic of Korea, it is reasonable to obtain confirmation from the notary consular officer of the overseas diplomatic mission. In this way, reinforcing the contents of personal information in the process of international marriage will play an important role in ensuring the stable marriage of multicultural families formed through international marriage brokerage. KCI Citation Count: 1